Comparison of ambulatory central hemodynamics and arterial stiffness in patients with diabetic and non‐diabetic CKD. Issue 12 (30th October 2020) - Loutradis, Charalampos; Schoina, Maria; Dimitroulas, Theodoros; Doumas, Michael; Garyfallos, Alexandros; Karagiannis, Asterios; Papagianni, Aikaterini; Sarafidis, Pantelis
Abstract: Increased arterial stiffness is independently associated with renal function decline in patients with diabetes mellitus (DM). Whether DM has additional deleterious effects on central hemodynamics and arterial stiffness in chronic kidney disease (CKD) patients is yet unknown. This study aimed to compare ambulatory central BP, arterial stiffness parameters, and trajectories between patients with diabetic and non‐diabetic CKD. This study examined 48 diabetic and 48 non‐diabetic adult patients (>18 years) with CKD (eGFR: <90 and ≥15 ml/min/1.73 m 2 ), matched in a 1:1 ratio for age, sex, and eGFR within CKD stages (2, 3a, 3b and 4). All patients underwent 24‐h ABPM with the Mobil‐O‐Graph device. Parameters of central hemodynamics [central systolic (cSBP) and diastolic blood pressure (cDBP), pulse pressure (PP)], wave reflection [augmentation index (AIx), and pressure (AP)] and pulse wave velocity (PWV) were estimated from the 24‐h recordings. Diabetic CKD patients had higher 24‐h cSBP (118.57 ± 10.05 vs. 111.59 ± 9.46, P  = .001) and 24‐h cPP (41.48 ± 6.80 vs. 35.25 ± 6.98, P  < .001) but similar 24‐h cDBP (77.09 ± 8.14 vs. 76.34 ± 6.75 mmHg, P  = .625) levels compared to patients with non‐diabetic CKD. During day‐ and nighttime periods, cSBP and cPP levels were higher in diabetics compared to non‐diabetics. 24‐h PWV (10.10 ± 1.62 vs. 9.61 ± 1.80 m/s, P  = .165) was numerically higher in patients with DM, but no between‐group differences were noted in augmentation pressure and index. In multivariate analysis, DM, female gender, and peripheral SBP were independently associated with higher cPP levels. Patients with diabetic CKD have higher ambulatory cSBP and increased arterial stiffness, as indicated by higher ambulatory cPP. These finding suggest that DM is a factor independently contributing to the adverse macrocirculatory profile of CKD patients.